Sintesis PAN-co-PMMA sebagai Compatibilizer pada Pencampuran Natural Rubber dan Nitrile Butadiene Rubber:Aplikasi dalam Pencampuran Karet Perapat - Megawati Fratiwi; Viona Aulia Rahmi; Sindi Wahyu Pratiwi; Maya Revanola Zainida; Rofiqoh Nur Rohmah (Jurnal Ilmiah Teknik Kimia, 2026)
Natural rubber (NR) and Nitrile Butadiene Rubber (NBR) exhibit poor miscibility due to their differences in their solubility parameters. To improve compatibility, a PAN-co-PMMA compatibilizer was synthesized by copolymerizing acrylonitrile (AN) and methyl methacrylate (MMA) with potassium persulfate (K2S2O8) as the initiator. This study investigates the influence of initiator concentration on the characteristics of PAN-co-PMMA and evaluates the mechanical performance of NR/NBR blends incorporating the compatibilizer for rubber seal applications. PAN-co-PMMA was synthesized using a water-ethanol co-solvent at 65°C for 3 hours with a stirring speed of 400 rpm, using initiator concentrations of 1, 2, 3, dan 4 %wt and an AN: MMA ratio of 90:10 (%wt). The drying was conducted at 100°C for 3 hours. IR analysis confirmed successful copolymerization through the appearance of characteristic C≡N and C=O absorption bands. The addition of PAN-co-PMMA reduced curing time and significantly enhanced the tensile strength of the NR/NBR blends.